2023
DOI: 10.1186/s12887-023-04026-w
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and environmental determinants of under-five child mortality in Ethiopia: using Ethiopian demographic and Health 2019 survey

Abstract: Background The under-five mortality rate is a reliable indicator of a country’s general level of development and the wellbeing of its children. Life expectancy is a good indicator of a population’s standard of living. Objectives To identify Socio-demographic and Environmental determinants of under-five child mortality in Ethiopia. Methods A national representative cross sectional study and a quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In 2020, the under-5 mortality rate was over 48.7 per 1,000 children in Ethiopia with just under 70,000 nursing personnel in the country. 10 While there are limited data on the overall disease burden of heart disease in children in Ethiopia, a 2017 cross-sectional study of six referral hospitals in Ethiopia, found the most common cardiac pathology was RHD followed by CHD. Of the patients with congenital heart defects, 35% had ventricular septal defects, 21% had atrial septal defects, 18% had patent ductus arteriosus, and 7% had tetralogy of Fallot.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, the under-5 mortality rate was over 48.7 per 1,000 children in Ethiopia with just under 70,000 nursing personnel in the country. 10 While there are limited data on the overall disease burden of heart disease in children in Ethiopia, a 2017 cross-sectional study of six referral hospitals in Ethiopia, found the most common cardiac pathology was RHD followed by CHD. Of the patients with congenital heart defects, 35% had ventricular septal defects, 21% had atrial septal defects, 18% had patent ductus arteriosus, and 7% had tetralogy of Fallot.…”
Section: Introductionmentioning
confidence: 99%